ОЦЕНКА ПРОФЕССИОНАЛЬНЫХ ФАКТОРОВ РИСКА ЗАБОЛЕВАЕМОСТИ COVID-19 МЕДИЦИНСКИХ РАБОТНИКОВ В ПЕРИОД ПАНДЕМИИ - Батов, Вячеслав Евгеньевич; Кузнецов, Сергей Максимович; Чернышов, Дмитрий Владимирович; Кертанов, Хетаг Алибекович (FORCIPE, 2022)